Rare Presentation of Gerbode Defect in a 4-Month-Old Nigerian and a Review of the Literature - Barbara E. Otaigbe; Douye Orubide (Case Reports in Cardiology)
A Gerbode defect is a very rare congenital anomaly which presents as a direct or an indirect type. We report a 4 month old Nigerian child who presented with poor feeding and failure to thrive and whose echocardiography confirmed an indirect Gerbode with a direct left ventricle to right atrial shunt due to adherent leaflets of the tricuspid valve. This was confirmed by surgery done outside the country.